Analisis Evaluasi Kinerja Aparatur Pemerintah Desa Dalam Rangka Menyelenggarakan Pemerintahan Desa Jatimulya, Kecamatan Kasokandel Kabupaten Majalengka - Amiruddin Setiawan; Fitria Mar’atul Janah (Jurnal Administrasi Publik Riset Inovatif, 2024)
A study was conducted to evaluate the performance of village officials in Jatimulya Village, Kasokandel District, Majalengka Regency. Using a descriptive qualitative method, the research analyzed the impact of officials' performance on local governance. Data were collected through interviews, observations, and literature. Informants included 2 village officials and 2 community members. Challenges identified were insufficient computer skills, lack of punctuality, task dependency, need for supervision, misunderstandings, lack of attentiveness, and underutilization of resources. Recommendations include training, task re-evaluation, improved discipline, computer skills enhancement, better resource use, and future preparedness.